In situ application of a cellulose bag and an ion exchanger for differentiation of labile and inert metal species in aquatic systems - Goveia, Danielle [UNESP]; Rosa, Andre Henrique [UNESP]; Bellin, Iramaia Correa; Lobo, Fabiana Aparecida [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Frutuoso Roveda, Jose Arnaldo [UNESP]; Cruz Romao, Luciane Pimenta; Dias Filho, Newton Luiz [UNESP] (Springer Heidelberg, 2008)
This work involved the development and application of a new analytical procedure for in-situ characterization of the lability of metal species in aquatic systems by using a system equipped with a diffusion membrane and cellulose organomodified with p-aminobenzoic acid groups (DM-Cell-PAB). To this end, the DM-Cell-PAB system was prepared by adding cellulose organomodified with p-aminobenzoic acid groups (Cell-PAB) to pre-purified cellulose bags. After the DM-Cell-PAB system was sealed, it was examined in the laboratory. The in-situ application involved immersing the DM-Cell-PAB system in two different rivers, enabling us to study the relative lability of metal species (Cu, Cd, Fe, Mn, and Ni) as a function of time and quantity of exchanger. The procedure is simple and opens up a new perspective for understanding environmental phenomena relating to the complexation, transport, stability, and lability of metal species in aquatic systems rich in organic matter.
Keywords: lability; metals; aquatic organic matter; water; speciation